Chapter Note al testo e alla traduzione - Cavalletto, Silvia (Studi di Traduzione Letteraria Lusofona, 2022)
The aim of this article is to offer a textual analysis of the short stories translated by Silvia Cavalletto and some very interesting notes regarding the Chinese translation of A China fica ao lado